Body mass index is similar to alternative anthropometric indices in evaluating plasma lipids as proxy for cardiovascular disease in women with previous hypertensive disorders of pregnancy: A cross-sectional study - Kristina Klepp; Anne Cathrine Staff; Meryam Sugulle; Kjartan Moe (Women's Health)
Background: Women with previous hypertensive disorders of pregnancy (HDP) have increased risk of cardiovascular disease (CVD). Overweight is a modifiable risk factor for both conditions. Anthropometric indices such as waist circumference, hip circumference, waist-to-hip ratio, estimated total body fat, a body shape index, waist-to-hip-to-height ratio, and index of central obesity improve estimation of cardiovascular death risk in the general population as compared to body mass index (BMI). Objectives: We aimed to assess whether alternative body mass composition indices associate more strongly with postpartum blood lipid levels, as a proxy for CVD risk, than BMI. We also aimed to investigate whether associations differ between women with previous normotensive or hypertensive index pregnancies. Design: In this cross-sectional study, we examined 296 women 1 or 3 years after an index pregnancy that was normotensive ( n  = 116) or complicated by a hypertensive pregnancy disorder, including preeclampsia ( n  = 133) or gestational hypertension ( n  = 47). Methods: Uni- and multivariable regression analyses, adjusted for age and smoking, were conducted to evaluate associations between postpartum body mass composition indices and blood lipids. p  < 0.05 was considered statistically significant. Results: Median BMI and overweight rates were higher in women with previous HDP than in controls (23.9 kg/m 2 versus 22.8 kg/m 2 and 44.4% versus 30.2%, both p  ⩽ 0.03). No body mass composition indices in any pregnancy complication group showed stronger associations with adverse lipid levels than BMI. However, women with previous HDP more often displayed significant associations between adverse body mass composition indices and adverse lipid levels, compared with controls. Conclusion: Alternative anthropometric measurements are not better suited to evaluate circulating lipids as proxy for CVD risk after HDP, compared to BMI. We hence recommend using BMI in CVD risk assessment after HDP due to its current widespread use and feasibility.